Evaluation Study on Khadi and Village Industries Programme - Planning Commission (Planning Commission, 2001)
During the Freedom Struggle, the development of Khadi and Village Industries was an instrument to meet the twin objective of self-reliance through local production and seeking active participation of the poor in the struggle for Independence through removal of hunger and unemployment. Their potential as an instrument of poverty alleviation was also recognised by our early planners.
Programme Evaluation Organisation, Planning Commission, Government of India